2000
DOI: 10.1097/00005373-200005000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Outcome from Injury: General Health, Work Status, and Satisfaction 12 Months after Trauma

Abstract: Twelve months after trauma, patients' work status, general health, and overall satisfaction with recovery are dependent on outcome mental health. This dependency persists despite measured baseline status, ISS, or physical recovery. The mental disease after trauma is attributable to poor mental health, the development of symptoms of PTSD and depression, and increased substance abuse. Trauma centers that fail to recognize, assess, and treat these injury-related mental health outcomes are not fully assisting thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
155
2
9

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 306 publications
(180 citation statements)
references
References 19 publications
14
155
2
9
Order By: Relevance
“…These propositions are supported by the literature indicating that when psychiatric disorders are co-morbid with traumatic injury, the associated disability is substantial. Many studies, including our own, have uncovered psychiatric disorders (Mason, Wardrope, Turpin, & Rowlands, 2002;Read et al, 2004) and disability after injury (Maraste, Persson, & Berntman, 2003;Smith et al, 2005) and demonstrated that psychiatric morbidity is a major contributor to this disability (Michaels et al, 2000).…”
Section: Introductionmentioning
confidence: 90%
“…These propositions are supported by the literature indicating that when psychiatric disorders are co-morbid with traumatic injury, the associated disability is substantial. Many studies, including our own, have uncovered psychiatric disorders (Mason, Wardrope, Turpin, & Rowlands, 2002;Read et al, 2004) and disability after injury (Maraste, Persson, & Berntman, 2003;Smith et al, 2005) and demonstrated that psychiatric morbidity is a major contributor to this disability (Michaels et al, 2000).…”
Section: Introductionmentioning
confidence: 90%
“…ASD, PTSD, and psychological distress are positively associated with wound healing and fatigue 13,[20][21][22][23][24][25] and negatively with quality of life (QOL) compared to the general population 18,[26][27][28][29][30][31] . Also, patients' satisfaction with work status, general health, and recovery from injury are related with impaired mental health, depressive symptoms, and increased risk of substance abuse 30,32 . As a result, the costs of care increases due to patients who needs more medical care, for example longer hospital stay after trauma or multiple hospital visits 25,33,34 .…”
mentioning
confidence: 99%
“…Also, patients' satisfaction with work status, general health, and recovery from injury are related with impaired mental health, depressive symptoms, and increased risk of substance abuse 30,32 . As a result, the costs of care increases due to patients who needs more medical care, for example longer hospital stay after trauma or multiple hospital visits 25,33,34 .In addition to QOL, PTSD, anxiety, and depression are most frequently examined after injury [26][27][28][29][30][31] . However, information about ASD is scarce.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] Few studies have described the use of health care services post-trauma, 1,6,7 and the relationship between health care service use and ongoing disability experienced by patients is unknown. Understanding the degree of disability experienced by trauma survivors and their pattern of support and outpatient services use is important for evaluating management approaches and improving health service provision.…”
mentioning
confidence: 99%